A retrospective study to evaluate biopsies of oral and maxillofacial lesions - Harkanwal Preet Singh; S H Thippeswamy; Piyush Gandhi; Varun Salgotra; Shivendra Choudhary; Ritika Agarwal (Wolters Kluwer Medknow Publications, 2021)
Background: The clinical manifestations of these lesions comprises pain, paresthesia, swelling, drainage, tooth loss, root resorption, and facial deformity. Alteration in oral and maxillofacial (OMF) tissues of the lesions may cause esthetically and functionally unfavourable effects in patients. Aims and Objectives: To determine the frequency of odontogenic cysts, tumors, and other lesions. Materials and Methods: Patient's records of histopathological reports from the archives of the Department of Oral and Maxillofacial Pathology were obtained and reviewed over a period of 2 years, and therefore, the lesions were classified into four groups. In cases of recurrent lesions, only the primary diagnosis was considered. The research protocol was approved by the ethical committee of the institution. Results: About 56.4% of males had ameloblastoma, 54.9% of females had cementoma. 59.4% females had giant cell granuloma, 87.5% females had pyogenic granuloma, 77.2% females had osteoma, 65.1% of the female population were belongs to the benign fibro-osseous lesions and 50.2% of females were from fibrous dysplasia in group 3. About 58.8% females had squamous cell carcinoma in group 4. Conclusion: To adequately determine the prevalence and incidence rate of OMF lesions, biopsies performed by other specialists such as otolaryngologists and plastic surgeons in OMF regions should also be evaluated.